The Role of microRNAs in Bovine Infection and Immunity - Lawless, Nathan; Vegh, Peter; O’Farrelly, Cliona; Lynn, David J. (Frontiers in Immunology, 2014)
MicroRNAs (miRNAs) are a class of small, non-coding RNAs that are recognised as critical regulators of immune gene expression during infection. Many immunologically significant human miRNAs have been found to be conserved in agriculturally important species, including cattle. Discovering how bovine miRNAs mediate the immune defence during infection is critical to understanding the aetiology of the most prevalent bovine diseases. Here, we review current knowledge of miRNAs in the bovine genome, and discuss the advances in understanding of miRNAs as regulators of immune cell function, and bovine immune response activation, regulation, and resolution. Finally, we consider the future perspectives on miRNAs in bovine viral disease, their role as potential biomarkers and in therapy.